Hubungan Antara Tingkat Kesenjangan Pendapatan dengan Pertumbuhan Ekonomi: Suatu Studi Lintas Negara - Joko Waluyo (Economic Journal of Emerging Markets, 2004)
This major topic in this study is relationships between income inequality and economic growth. The study will examine the relationships between income inequality and growth via investment impact to redistribution,. This model spefisification from endogenous growth model with capital market imperfection exist, in notation with single equation linier model. Data from Deininger data base, cross section data for 60 countries. We  estimate  this regression model with OLS with Newey-West HAC standard error and fulfill CLRM assumption. This result are: a) The relationships income inequality, asset inequality with growth are negative and significant. b) Investment does not have positive impact with income redistribution, but give impact to increase resource allocation efficiency. Keywords: Income inequolity, economic growth, capital market imperfection.